Kemudahan Transaksi Digital: Transformasi Preferensi Pembayaran Konsumen - Erna Shaira Fadilah; Agus Munandar (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The current digital era is influencing and driving fundamental changes in various aspects of life, including the way consumers conduct payment transactions. Fast, efficient, and secure payment systems are essential in this digital age. The shift from traditional methods to more innovative ones, along with the convenience, speed, and security offered through the application of digital technology, supports the transformation of payment preferences. This article aims to analyze the factors driving changes in consumer payment preferences in the digital era, which facilitate transactions, the role of various payment technologies, and the challenges posed by future trends in digital payments. Trend analysis and literature review were conducted to provide an understanding of consumer payment transformation. The results of this study indicate that the ease of digital transactions is currently transforming payment preferences and is an inevitable development, driven by convenience or practicality, speed, security, and the demands of lifestyle integration, which are increasingly driving consumers to cashless payments, whether using e-wallets or mobile banking.